Incoterms® 2020 : ICC rules for the use of domestic and international trade terms - International Chamber of Commerce (International Chamber of Commerce, 2024)
This book contains the ICC rules for use of the 11 Incoterms trade terms. It takes into account the latest developments in commercial practice, and updates the rules to make them more accessible and easier to use